Damage Analysis of Low-Velocity Impact of Non-Woven Flax Epoxy Composites. Issue 11 (1st November 2020) - Habibi, Mohamed; Selmi, Saber; Laperrière, Luc; Mahi, Hojjat; Kelouwani, Sousso
ABSTRACT: This paper presents an experimental study of the low-velocity impact behavior and the post-impact residual tensile properties of a non-woven flax epoxy composite. The effect of impact on shape was investigated based on varying impact angle and then correlated to the impact energy. A significant effect of these two parameters on the induced-damage type and shape, the impactor penetration depth and the damaged area were obtained. The composites were subsequently subjected to tensile test it was found that tensile stress and strain decrease with increasing impact energy, especially after 3 J where the material deformation and the local strain are highly influenced.